Islamic marketing strategy: eradicating rural poverty in Malaysia - Al Harran , Saad Abdul SattaR; Zakaria, Mustafar; Khalid, Haniza (Pelanduk Publications, 1994)
This applied research work is new and on of tis kind in Malaysia. It seeks to identify the causes for prolonged condition of poverty in the fishing villages of Malaysia despite vigorous efforts by numerous government and non-government bodies. It introduces the Islamic financing model, Musyarakah, as in integrated approach to grassroot development. Poverty solution does not lie only in improving facilities and mechanisms, but in bringing about a fresh outlook of life and the the same time establishing a fair and just society for all; irrespective of economic, social or political background.